Paradigma Fikih Qur’anik dalam Manajemen Konflik Keluarga: Qur'anic Fiqh Paradigm in Family Conflict Management - Aziz, Muhammad Aziz; Abdul Aziz Harahap (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
Various forms of conflict in family life require serious handling through various approaches and perspectives. This research is present to describe the perspective of Quranic fiqh related to conflict management on the problems of family life. This research is a qualitative research in the form of a literature study with a content analysis approach combined with a thematic interpretation approach. Data is collected using documentation techniques, and data analysis techniques are carried out through inventory, classification, and interpretation. The results found that there are at least two legal provisions in the Qur'an that can be a paradigm in the process of resolving household conflicts, namely the preventive and curative paradigms. The preventive paradigm can be manifested through tolerance of each other's shortcomings, flexible division of roles, and strengthening of foundations. Meanwhile, the curative paradigm can be manifested through reminding and reprimanding, using mediators, negotiating, and divorce as the last resort to achieve benefits. The findings of this study show that as the main source of Islamic law (fiqh), the Qur'an contains various verse messages related to legal provisions that can be a paradigmatic basis in family conflict management.